Typology of regional units based on RES plants: The case of Greece. (October 2017) - Arabatzis, Garyfallos; Kyriakopoulos, Grigorios; Tsialis, Panagiotis
Abstract: The development and the utilization of Renewable Energy Sources (RES) are outmost importance targets of European strategic plans in the context of sustainable development. Greece sustains a plentiful abundance of RES, which should be proven advantageous towards a gradual independence from the fossil fuels based on an ongoing exploitation of all RES, accordingly. This study aims at developing a typology of the regional units (NUTS III) of Greece based on the number and respective installed power of RES plants for the production of electricity. The clustering of the Greek regional units (former prefectures) is accomplished by using the multivariate statistical method of cluster analysis and, more specifically, through hierarchical cluster analysis. The hierarchical cluster analysis resulted in five clusters, each featuring different characteristics. The first cluster consists of nineteen regional units located in mainland Greece. The majority of electricity generating plants from RES are found in this cluster. The second cluster comprises eighteen regional units, most of which are located on islands. This cluster includes a large number of wind plants, of low power however. The third cluster consists of six regional units and is characterized by a large number of high power wind plants. The fourth cluster includes seven regional units, which are all located in mainland Greece. A characteristic feature of this cluster is the fact that it includes most biomass plants, and the majority of small hydropower plants. The fifth cluster only comprises one regional unit, Attiki, where the capital of Greece is located.